Laser-based 3D printing and optical characterization of optical micro-nanostructures inspired by nocturnal insects compound eyes - Bogdan Stefanita Calin; Roxana Cristina Popescu; Eugenia Tanasa; Irina Alexandra Paun (Scientific Reports)
Abstract Nature offers unique examples that help humans produce artificial systems which mimic specific functions of living organisms and provide solutions to complex technical problems of the modern world. For example, the development of 3D micro-nanostructures that mimic nocturnal insect eyes (optimized for night vision), emerges as promising technology for detection in IR spectral region. Here, we report a proof of principle concerning the design and laser 3D printing of all ultrastructural details of nocturnal moth Grapholita Funebrana eyes, for potential use as microlens arrays for IR detection systems. Optimized computer-aided design and laser writing parameters enabled us to reproduce the entire complex architecture of moth compound eyes, with submicrometric spatial accuracy. As such, the laser-imprinted structures consisted in ommatidia-like microstructures with average diameter of about 14 μm, decorated with nipple-like nanopillars between 200 and 400 nm in height and average periodicity of around 450 nm. The dimensions of moth-eye inspired structures deviated by less than 10% from the natural corresponding structures. The optical properties of the moth eyes-inspired microlens arrays were investigated in the infrared (IR) range, between 1000 and 1700 nm. The optical transmission of microlens arrays with nanopillars was up to 17.55% higher than the transmission through microlens arrays without nanopillars. Moreover, the reflection of nanopillar-decorated microlens arrays was up to 0.91% lower than the reflection for microlenses without nanopillars. In addition, the focal spot diameter at 1/e2 for nanopillar—decorated microlens arrays was of 7.64 μm, representing and improvement of 16.5% of focal spot diameter as compared to microlens arrays without nanopillars. Similarly with the IR region, the reflection measured in the Visible range was higher for microlense arrays with nanopillars than the reflection through microlenses arrays without nanopillars. In contrast, in the Visible range the transmission of nanopillar-decorated microlens arrays was lower than the one for microlense arrays without nanopillars, which could be, most likely, assigned to diffraction losses on the nanopillars.